Pelatihan Pembuatan Coklat Mete Untuk Meningkatkan Nilai Jual Sehingga Meningkatkan Penghasilan Masyarakat - M. Rimawan; Alwi Alwi; Puji Muniarty (Institut Teknologi dan Bisnis Semarang, 2024)
One way to increase the price value of natural resources produced by the Kore village community, especially cashew nuts, is by processing cashew nuts into cashew chocolate to increase the community's creative ideas in processing cashew nuts into a snack product that can be sold in the market or in shops. generally. In this case, students offer attractive packaging so as to increase consumer purchasing power. Then, in terms of packaging, Korean people don't really pay attention, so we are here to offer the public, if the product is to be suitable and considered attractive, it must be with attractive packaging, in addition to considering the needs for making the product so that we can determine a price that is in accordance with the expenditure and the unit price of the product to be sold. . This training will increase the community's experience and insight in developing the natural resources around them into business ideas.